"Housing is such a major part of someone's life": mental health social work practice in the context of a housing affordability crisis. Issue 1 (2nd January 2023) - Tseris, Emma; Brasser, Emmylou; Tully, Simon; Jackson, Melinda; Ferguson, Lindsay
ABSTRACT: It is well-known that people with psychiatric diagnoses experience disproportionate rates of homelessness. However, few studies have explored the perspectives and practices of mental health social workers in responding to clients experiencing homelessness. This article reports on findings from three focus groups with inpatient mental health social workers in Sydney, Australia. Three themes were identified: stuck in a crisis; reliance on sub-standard housing conditions; and pressures to discharge. The study reveals the challenges experienced by social workers in navigating scarce housing resources, and the limitations of a biomedical paradigm in failing to address the social determinants of mental distress.